Cajun French phonologies in Louisiana today - Babatsouli, Elena (Journal of Monolingual and Bilingual Speech, 2024)
The speech sounds of endangered Cajun French (CF), as it survives in Louisiana today, are investigated in the present study. Sixteen fluent CF Heritage Language speakers (seven males, nine females), of an average age of 77 years, who live in Lafayette parish, Louisiana, picture-named 50 words of varying CF-representative phonotactics. On average, 34 words were produced similarly by 67% of participants and 16 words were produced similarly by 29% of participants. Variation mainly targets vowels, glides, affricates, and the rhotic, with prevalent processes occurring in stressed closed syllables. Results profile phonemic and phonetic inventories documenting CF phonologies today, also highlighting differences from earlier reports.